Nitrogen-phosphorus co-doped iron-nickel-based porous biomass charcoal catalyst as well as preparation method and application thereof
Through self-assembly precipitation and in-situ pyrolysis technology, nitrogen and phosphorus co-doped iron-nickel-based porous biomass carbon catalyst was prepared, which solved the low conductivity and stability of nickel-based catalysts in oxygen reduction reaction, and achieved efficient oxygen evolution The catalytic performance of the reaction has good application value for hydrogen energy utilization.
Patent Information
- Application Number
- CN202411681624.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The existing nickel-based catalysts have low conductivity and stability problems in oxygen reduction reactions, which limits their application in electrochemical water decomposition.
Through self-assembly precipitation and in-situ pyrolysis technology, a nitrogen-phosphorus co-doped iron-nickel-based porous biomass carbon catalyst is prepared. The catalyst has a three-dimensional network porous structure, high specific surface area and porosity, and has many active sites, which significantly improves the catalysis performance.
This catalyst exhibits excellent catalytic performance in the oxygen evolution reaction, low overpotential, high catalytic activity, high reaction efficiency, and has good application value in realizing the efficient utilization of hydrogen energy.
Smart Images

Figure CN119465231A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalytic materials, and in particular relates to a nitrogen-phosphorus co-doped iron-nickel based porous biomass carbon catalyst and a preparation method and application thereof. Background Art
[0002] With the intensification of the energy resource crisis and the pressure of environmental pollution, the development and utilization of new energy and the high-value utilization of green resources are particularly important. Hydrogen energy, as a clean and pollution-free new energy, is produced, stored and utilized through electrochemical reactions such as fuel cells, metal-air batteries and water splitting. The oxygen evolution reaction (OER) plays an important role and is a key step in electrochemical water splitting. During this reaction, the OH bond breaks and the OO bond forms, resulting in the formation of a high energy barrier. However, it requires a large overpotential, resulting in slow kinetics, so a catalyst is needed to accelerate the reaction. Currently, the most effective electrocatalysts are made of precious metals such as platinum, iridium and ruthenium. However, their limited supply, controlled deposition, scarcity and high cost greatly limit their commercial application. Therefore, it is necessary to develop catalysts that are easy to synthesize, have minimal interference, are easy to cooperate and show high efficiency in OER, which is crucial to achieve efficient utilization of hydrogen energy.
[0003] A large number of research results show that transition metal elements such as Fe, Co and Ni are highly active in OER. They are widely distributed, low-cost, and have significantly better catalytic stability than precious metals, and are gradually becoming substitutes for precious metal materials. For example, the paper "Preparation and Performance Study of Nitrogen-Phosphorus Co-doped Iron-based Biomass Carbon Catalyst for Oxygen Reduction Reaction (ORE)" discloses a novel catalyst with bagasse as carbon source, phytic acid as phosphorus source, melamine as nitrogen source, Fe(NO 3 ) 3 9H 2 O as the iron source, phosphorus and nitrogen co-doped iron-based biomass carbon materials with hierarchical porous carbon microspheres were prepared by a simple hydrothermal and co-pyrolysis method and applied to oxygen reduction reaction. Studies on transition metal electrocatalysts have found that the binding energy of Ni, Co, and Fe-based catalysts is moderate, second only to precious metals, and nickel-based compounds are widely used in energy generation and storage devices due to their excellent catalytic performance, good electrical properties, low cost, and easy access. However, the main problem at present is the low conductivity and stability of nickel-based catalysts for OER.
[0004] To solve this problem, Ni can form alloys with other 3d transition metals, which can improve the electronic and structural properties of the catalyst, and the catalytic performance of binary alloys is better than that of single transition metals. The addition of adjacent Fe atoms changes the electronic structure of the surface Ni atoms, thereby improving the OER activity. Nickel-iron alloying is a better choice for developing highly active and stable water oxidation electrocatalysts, and its performance is better than that of a single catalyst. For example, patent publication number CN 116314857 A discloses a method for preparing an iron-nickel alloy / nitrogen-doped carbon nanocomposite electrocatalyst. During the preparation process, uniform FeNi alloying active sites are formed in FeNi-CNC, which can improve the ORR / OER electrocatalytic activity of the composite material, which is better than commercial Pt / C catalysts. Therefore, the synergistic use of FeNi binary alloys and carbon supports is an effective method to improve the catalytic OER performance at a lower cost.
[0005] The performance of porous carbon materials as electrodes depends on the chemical nature of the OER-active pyridinic N and ORR-active quaternary N groups that result in a high density, as well as the porosity of the material. These factors determine the exposure of the active sites to the relevant chemicals and help prevent rapid clogging of the planar electrode surface. Transition metal phosphides (TMPs) are promising catalysts for OER reactions due to their high conductivity and good electrochemical performance. Phosphorus-containing compounds have high electronegativity and weak metal-phosphorus bond dissociation, making them susceptible to surface remodeling. The P element in metal phosphides has two functions. First, it acts as a hydride acceptor to promote hydrogen adsorption; second, it modulates the adsorption characteristics of surrounding metal atoms by donating or withdrawing electrons, thereby changing their electron density. In metal phosphides, the metal usually has two additional functions. One is to act as a proton acceptor, and the other is to enhance the conductivity of the catalyst. Therefore, the phosphorus-doped sites can adjust the charge distribution of the carbon skeleton and FeNi / N, thereby optimizing the adsorption and desorption capacity of intermediates and products, and ultimately improving the activity of the catalyst. Summary of the invention
[0006] In view of the above problems, the present invention provides a nitrogen and phosphorus co-doped iron-nickel based porous biomass carbon catalyst and a preparation method and application thereof. The nitrogen and phosphorus co-doped iron-nickel based porous biomass carbon catalyst is prepared by self-assembly precipitation and in situ pyrolysis. The catalyst has a three-dimensional network porous structure, high specific surface area and porosity, many active sites, and good catalytic performance in oxygen evolution reaction.
[0007] The present invention is achieved through the following technical solutions:
[0008] A nitrogen-phosphorus co-doped iron-nickel based porous biomass carbon catalyst is prepared by subjecting biomass carbon to a hydrothermal reaction to obtain hydrothermal carbon, which is then cold-alkali activated to obtain cold-alkali activated hydrothermal carbon as a carbon source, and Fe and Ni are in situ complexed on the carbon source to obtain a precursor, which is then co-doped with N and P, and calcined at a high temperature to obtain a nitrogen-phosphorus co-doped iron-nickel based porous biomass carbon catalyst.
[0009] Furthermore, the nitrogen-phosphorus co-doped iron-nickel-based porous biomass carbon catalyst is a three-dimensional network porous structure with a specific surface area of 160 to 163 m 2 / g, pore volume is 0.15~0.18cm 3 / g, and the average pore size is 5.5~7.4nm.
[0010] A method for preparing the nitrogen-phosphorus co-doped iron-nickel based porous biomass carbon catalyst as described above comprises the following steps:
[0011] (1) Preparation of hydrothermal charcoal: sugarcane bagasse is added to a hydrochloric acid solution, stirred, and then transferred to a reactor for hydrothermal reaction. After the reaction is completed, the mixture is naturally cooled to room temperature, and the obtained product is washed and dried to obtain hydrothermal charcoal;
[0012] (2) cold alkali activated hydrothermal carbon: placing the hydrothermal carbon in step (1) in a NaOH solution for cold alkali activation, and after the activation, centrifuging, washing and drying to obtain cold alkali activated hydrothermal carbon;
[0013] (3) Synthesis of precursor: Fe(NO 3 ) 3 9H 2 O and Ni(CH 3 COO 2 ·4H 2 O is dissolved in water, and after vigorous stirring and mixing, the obtained mixed solution is added dropwise to the aqueous solution of cold alkali activated hydrothermal carbon in step (2), and after stirring, the pH of the solution is adjusted to alkaline, and after suction filtration, the obtained product is washed and dried to obtain a precursor;
[0014] (4) Nitrogen and phosphorus co-doping: The precursor of step (3) is mixed with urea and uniformly ground, and sodium dihydrogen phosphate is added, followed by high-temperature calcination. After the calcination, the mixture is cooled to room temperature to obtain a nitrogen and phosphorus co-doped iron-nickel-based porous biomass carbon catalyst.
[0015] Furthermore, in step (1), the mass ratio of bagasse to hydrochloric acid solution is 4 g:40-45 mL, and the concentration of hydrochloric acid solution is 0.1-0.15 mol / L.
[0016] Furthermore, in step (1), the temperature of the hydrothermal reaction is 210-230° C., and the time is 10-12 hours.
[0017] Furthermore, in step (2), the mass ratio of the hydrothermal charcoal to the NaOH solution is 2.5 g:45-50 mL, the concentration of the NaOH solution is 1.3-1.5 mol / L; and the cold alkali activation time is 1.5-2 h.
[0018] Furthermore, in step (3), the Fe(NO 3 ) 3 9H 2 O and Ni(CH 3 COO 2 ·4H 2 The mass ratio of O is 2.3:1.3-1.6; the mass ratio of cold alkali activated hydrothermal carbon to water in the aqueous solution of the cold alkali activated hydrothermal carbon is 1g:100-120mL.
[0019] Furthermore, in step (4), the mass ratio of the precursor, urea and sodium dihydrogen phosphate is 5:3-4:100-120.
[0020] Furthermore, in step (4), the high temperature calcination is calcined in a nitrogen atmosphere at 280-300° C. for 1.5-2 h, and then the temperature is raised to 700-800° C. and maintained for 1.5-2 h.
[0021] An application of the nitrogen-phosphorus co-doped iron-nickel based porous biomass carbon catalyst as described above in catalytic oxygen evolution reaction.
[0022] The preparation principle of the nitrogen and phosphorus co-doped iron-nickel based porous biomass carbon catalyst of the present invention is as follows:
[0023] (1) Preparation of hydrothermal charcoal: Sugarcane bagasse is added to a hydrochloric acid solution and subjected to a hydrothermal reaction. The cellulose, hemicellulose and lignin in the bagasse are first decomposed into sugars and other small molecules, which are then transformed into more complex structures through a series of hydrolysis and polymerization reactions. During the hydrothermal treatment process, the small molecules formed will further dehydrate and polymerize, eventually forming a carbon-rich solid substance, namely hydrothermal charcoal.
[0024] (2) Cold alkali activation of hydrothermal carbon: Placing the hydrothermal carbon in a NaOH solution for cold alkali activation can increase the oxygen-containing functional groups (such as hydroxyl and carboxyl) of the hydrothermal carbon, enhance the surface chemical activity of the carbon-based material, and provide additional catalytic sites.
[0025] (3) Synthesis of precursor: Fe(NO 3 ) 3 9H 2 O and Ni(CH 3 COO 2 ·4H 2O is dissolved in water, and the resulting mixed solution is added dropwise to the aqueous solution of cold alkali activated hydrothermal carbon. In this process, Fe 2+ and Ni 2+ The ions form stable coordination compounds in water, which are combined with cold alkali activated hydrothermal carbon by ion exchange or adsorption, and the pH of the solution is adjusted to alkaline, so that the metal ions are precipitated or form nanoparticles and form a composite structure on the surface of the hydrothermal carbon.
[0026] (4) Nitrogen-phosphorus co-doping: The precursor is mixed and ground with urea, and then sodium dihydrogen phosphate is added. The urea decomposes to produce ammonia, which reacts with the carbon material to form a nitrogen-doped structure. At the same time, sodium dihydrogen phosphate also begins to decompose, and then high-temperature calcination is performed to further promote the formation of phosphoric acid and the fixation of phosphorus in the carbon structure. At the same time, high temperature helps to form more stable metal oxides and more developed pore structures. The introduction of nitrogen and phosphorus heteroatoms can change the charge density and spin density of carbon atoms and increase active sites. At the same time, nitrogen and phosphorus doping can produce a synergistic effect, thereby improving the reduction performance of carbon materials.
[0027] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0028] 1. The present invention prepares nitrogen-phosphorus co-doped iron-nickel-based porous biomass carbon catalyst by self-assembly precipitation and in-situ pyrolysis, specifically, the biomass carbon is subjected to hydrothermal reaction to obtain hydrothermal carbon, the obtained hydrothermal carbon is subjected to cold alkali activation to obtain cold alkali activated hydrothermal carbon as a carbon source, Fe and Ni are in-situ complexed on the carbon source to obtain a precursor, and then the precursor is co-doped with N and P, and after high-temperature calcination, a nitrogen-phosphorus co-doped iron-nickel-based porous biomass carbon catalyst is obtained. The catalyst is a three-dimensional network porous structure with a specific surface area of 160 to 163 m 2 / g, pore volume is 0.15~0.18cm 3 / g, with an average pore size of 5.5-7.4nm, high specific surface area and porosity, and many active sites, and has good catalytic performance in oxygen evolution reaction.
[0029] 2. The present invention uses N-doped bagasse to derive carbon layer FeNi alloy, which helps to optimize the electronic structure and enhance electron transfer. 2 PO 3 PH generated during pyrolysis 3 The gas is fully mixed with the carbon material at high temperature and low gas velocity to form a porous structure. The activated surface area of this type of microstructured catalytic layer is larger than that of pure carbon nanoporous structure, which can provide more catalytic active sites for oxygen evolution reaction.
[0030] 3. The catalyst of the present invention is a carbon material doped with N, P, Fe and Ni heteroatoms, assembled from nanoparticles, and is a porous bimetallic nitrogen phosphide with a three-dimensional network porous structure and high-density electrochemical active sites. The pore structure of the catalyst is mesoporous, and this porous structure can provide more reaction sites for the oxygen evolution reaction and improve the molecular diffusion efficiency.
[0031] 4. The catalyst of the present invention is applied to oxygen evolution reaction, and its -2 It exhibits excellent catalytic performance at a current density of , and the overpotential in the oxygen evolution reaction is as low as 291mV. It has high catalytic activity and high reaction efficiency, and has great application value for realizing the efficient utilization of hydrogen energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 These are the XRD diagrams of FeNi / AHC-NP, FeNi / HC-N, FeNi / HC-P and FeNi / HC prepared in Example 1 and Comparative Examples 1-3, respectively.
[0033] Figure 2 This is the SEM image of FeNi / AHC-NP prepared in Example 1.
[0034] Figure 3 This is the EDS element distribution diagram of FeNi / AHC-NP prepared in Example 1.
[0035] Figure 4 N is the FeNi / AHC-NP prepared in Example 1 2 Adsorption-desorption isotherms and pore size distribution curves.
[0036] Figure 5 The OER-LSV curves and Tafel slope diagrams of FeNi / AHC-NP, FeNi / HC-N, FeNi / HC-P and FeNi / HC in Application Example 1 and Comparative Examples 1-3 are shown. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below by way of examples. These examples are only used to illustrate the present invention and do not limit the protection scope of the present invention.
[0038] Example 1
[0039] Preparation of Nitrogen and Phosphorus Co-doped Iron-Ni Based Porous Biochar Catalyst:
[0040] (1) Preparation of hydrothermal charcoal: 4 g of bagasse was added to 40 mL of 0.1 mol / L hydrochloric acid solution and stirred for 4 h. The mixture was then placed in a 100 mL polytetrafluoroethylene liner of a hydrothermal autoclave. The autoclave was placed in an oven at 220 °C for 12 h. After the reaction was completed, the mixture was naturally cooled to room temperature, washed with water and ethanol in turn, and dried to obtain hydrothermal charcoal (denoted as HC).
[0041] (2) Cold alkali activated hydrothermal carbon: 2.5 g of hydrothermal carbon was placed in 50 mL of 1.5 mol / L sodium hydroxide solution for activation for 2 h. After activation, the carbon was centrifuged, washed, and dried to obtain cold alkali activated hydrothermal carbon (denoted as AHC).
[0042] (3) Synthesis of precursor: 2.302 g Fe(NO 3 ) 3 9H 2 O and 1.434g Ni(CH 3 COO 2 ·4H 2 O was vigorously stirred into 50 mL of pure water, and was added dropwise into a 1 g / 100 mL aqueous solution of cold alkali activated hydrothermal carbon. After stirring for 10 min, the pH was adjusted to 8, filtered, washed, and washed with ultrapure water until neutral, and then dried at 80 ° C for 24 h to obtain a precursor.
[0043] (4) Nitrogen-phosphorus co-doping: 50 mg of the precursor and 30 mg of urea were mixed and evenly ground, 1 g of sodium dihydrogen phosphate was added upstream, and the mixture was calcined at 300 °C in a nitrogen atmosphere for 2 h, then heated to 800 °C and maintained for 2 h, and cooled to room temperature to obtain a nitrogen-phosphorus co-doped iron-nickel-based porous biochar catalyst (denoted as FeNi / AHC-NP).
[0044] Example 2
[0045] Preparation of Nitrogen and Phosphorus Co-doped Iron-Ni Based Porous Biochar Catalyst:
[0046] (1) Preparation of hydrothermal charcoal: 4 g of bagasse was added to 45 mL of 0.1 mol / L hydrochloric acid solution and stirred for 4 h. The mixture was then placed in a 100 mL polytetrafluoroethylene liner of a hydrothermal autoclave. The hydrothermal autoclave was placed in an oven at 210 °C for 12 h. After the reaction was completed, the mixture was naturally cooled to room temperature, washed with water and ethanol in turn, and dried to obtain hydrothermal charcoal.
[0047] (2) Cold alkali activated hydrothermal carbon: 2.5 g of hydrothermal carbon was placed in 45 mL of 1.5 mol / L sodium hydroxide solution for activation for 2 h. After activation, the carbon was centrifuged, washed, and dried to obtain cold alkali activated hydrothermal carbon.
[0048] (3) Synthesis of precursor: 2.301 g Fe(NO 3 )3 9H 2 O and 1.375 g Ni(CH 3 COO 2 ·4H 2 O was vigorously stirred into 50 mL of pure water, and was added dropwise into a 1 g / 110 mL aqueous solution of cold alkali activated hydrothermal carbon. After stirring for 10 min, the pH was adjusted to 8, filtered, washed, and washed with ultrapure water until neutral, and then dried at 80 ° C for 24 h to obtain a precursor.
[0049] (4) Nitrogen-phosphorus co-doping: 50 mg of the precursor and 35 mg of urea were mixed and evenly ground, 1.1 g of sodium dihydrogen phosphate was added upstream, and the mixture was calcined at 280 °C in a nitrogen atmosphere for 2 h, then heated to 700 °C and maintained for 2 h, and cooled to room temperature to obtain a nitrogen-phosphorus co-doped iron-nickel-based porous biochar catalyst.
[0050] Example 3
[0051] Preparation of Nitrogen and Phosphorus Co-doped Iron-Ni Based Porous Biochar Catalyst:
[0052] (1) Preparation of hydrothermal charcoal: 4 g of bagasse was added to 40 mL of 0.15 mol / L hydrochloric acid solution and stirred for 4 h. The mixture was then placed in a 100 mL polytetrafluoroethylene liner of a hydrothermal autoclave. The hydrothermal autoclave was placed in an oven at 230 °C for 10 h. After the reaction was completed, the mixture was naturally cooled to room temperature, washed with water and ethanol in turn, and dried to obtain hydrothermal charcoal.
[0053] (2) Cold alkali activated hydrothermal carbon: 2.5 g of hydrothermal carbon was placed in 45 mL of 1.3 mol / L sodium hydroxide solution for activation for 1.5 h. After activation, the carbon was centrifuged, washed, and dried to obtain cold alkali activated hydrothermal carbon.
[0054] (3) Synthesis of precursor: 2.302 g Fe(NO 3 ) 3 9H 2 O and 1.571 g Ni(CH 3 COO 2 ·4H 2 O was vigorously stirred into 50 mL of pure water, and was added dropwise into a 1 g / 120 mL aqueous solution of cold alkali activated hydrothermal carbon. After stirring for 10 min, the pH was adjusted to 8, filtered, washed, and washed with ultrapure water until neutral, and then dried at 80 ° C for 24 h to obtain a precursor.
[0055] (4) Nitrogen-phosphorus co-doping: 50 mg of the precursor and 40 mg of urea were mixed and evenly ground, 1.2 g of sodium dihydrogen phosphate was added upstream, and the mixture was calcined at 290 °C in a nitrogen atmosphere for 1.5 h, then heated to 750 °C and maintained for 1.5 h, and cooled to room temperature to obtain a nitrogen-phosphorus co-doped iron-nickel-based porous biochar catalyst.
[0056] Comparative Example 1
[0057] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, no sodium dihydrogen phosphate is added in step (4), and the rest of the preparation process and conditions are the same as those of Example 1, to obtain a nitrogen-doped iron-nickel based biomass carbon catalyst (denoted as FeNi / AHC-N).
[0058] Comparative Example 2
[0059] The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, urea is not added in step (4), and the rest of the preparation process and conditions are the same as those of Example 1, to obtain a phosphorus-doped iron-nickel-based biomass carbon catalyst (denoted as FeNi / AHC-P).
[0060] Comparative Example 3
[0061] The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, urea and sodium dihydrogen phosphate are not added in step (4), and the rest of the preparation process and conditions are the same as those of Example 1 to obtain an iron-nickel based biomass carbon catalyst (denoted as FeNi / AHC).
[0062] Material Characterization Analysis
[0063] (I) X-ray diffraction (XRD) analysis
[0064] The FeNi / AHC-NP, FeNi / HC-N, FeNi / HC-P and FeNi / HC prepared in Example 1 and Comparative Examples 1-3 were characterized and analyzed by X-ray diffractometer (XRD) to reveal the crystal structure of the prepared samples. The characterization results are as follows: Figure 1 As shown. Figure 1It can be seen that the doping of N, P or NP has a significant effect on the phase composition and crystal structure of the final sample. When the sample is not doped with N, P or NP, the samples NiFe@C and NiFe@C-NaOH simultaneously generate diffraction peaks of nickel ferrite (PDF#99-000-3769) and Ni (PDF#04-002-752). When the sample is doped with N, P or NP, the diffraction peaks of these samples at 2θ=43.6°, 50.8°, 74.7° and 90.7° are related to the (111), (200), (220) and (311) planes of the face-centered cubic (fcc) FeNi alloy (04-002-1863). The main reason may be that they improve the adsorption capacity of metal ions, provide a reducing environment and stabilize metal nanoparticles.
[0065] (ii) Scanning electron microscopy (SEM) analysis
[0066] The FeNi / AHC-NP prepared in Example 1 was characterized and analyzed using a scanning electron microscope (SEM). Figure 2 shown. Figure 2 (a), 2(b), and 2(c) are carbon microsphere structures magnified 2000 times, 5000 times, and 10000 times, respectively. Figure 2 (d), 2(e), and 2(f) are the flake morphologies magnified 2000 times, 5000 times, and 10000 times, respectively. Figure 2 (a), 2(b), and 2(c) show that the samples treated with hydrochloric acid show obvious carbon microsphere structure. This is because the cellulose and hemicellulose in bagasse are hydrolyzed under acidic conditions to form water-soluble products, which are then dehydrated, polymerized, condensed, and aromatized under hydrothermal pressure to form carbon microspheres. Figure 2 (d), 2(e), and 2(f) show the flake structure of bagasse biomass materials. Compared with the flake morphology, the flake morphology has a higher specific surface area, which can expose more active sites. The surface of the composite FeNi / AHC-NP is uneven, and the geometry of carbon nanopores and particles is irregular. On the one hand, bagasse-derived carbon as a carbon carrier of catalyst material has the advantage of natural porous carbon materials and can provide rich pore structure for the catalyst. On the other hand, NaH 2 PO 2 PH generated during pyrolysis 3 The gas is fully mixed with the carbon material precursor at high temperature and low gas flow rate. The activated surface area of this microstructured catalyst layer is larger than that of pure carbon nanoporous structure, which can provide more catalytic active sites for oxygen evolution reaction. The particles have better adhesion to the catalyst cross section and between the catalyst layer and the substrate. The fine nanoparticles (white phase) are more evenly embedded in the pores and between the catalyst layer and the substrate.
[0067] (III) Energy dispersive spectroscopy (EDS) analysis
[0068] The FeNi / AHC-NP prepared in Example 1 was characterized and analyzed by energy dispersive chromatograph (EDS). The characterization results are as follows: Figure 3 As shown. Figure 3 It can be seen that FeNi / AHC-NP 2 It is composed of C, O, Fe, Ni, N and P, and is evenly distributed in the composite material.
[0069] (IV) Specific surface area and pore size analysis
[0070] The specific surface area and pore size of FeNi / AHC-NP prepared in Example 1 were analyzed. Figure 4 As shown. Figure 4 It can be seen that the Brunauer-Emmett-Teller (BET) of FeNi / AHC-NP, Figure 4 (a) Typical type IV adsorption isotherms and H1 hysteresis loops can be observed, which are the characteristics of mesoporous structures. The BET area reaches 161 m 2 / g, pore volume is 0.15~0.16cm 3 / g, with an average pore size of 5.5-7.4 nm, which can provide an electrocatalytically active surface and expose active sites during the oxygen evolution reaction. Figure 4 (b) shows that the pore size of FeNi / AHC-NP is mainly distributed in mesopores, although macropores also exist. This porous structure can provide more reaction sites for oxygen evolution and improve the molecular diffusion efficiency. The formation of a certain surface area and porous structure can improve the catalytic activity of oxygen evolution reaction and accelerate electron migration.
[0071] (V) Elemental composition and atomic ratio analysis
[0072] Elemental analysis of HC and AHC in Example 1 is shown in Table 1 below.
[0073] Table 1 Elemental composition and atomic ratio of HC and AHC
[0074]
[0075] As shown in Table 1, after HC is activated by cold alkali, AHC is obtained. The content of oxygen in AHC is significantly increased, and the O / C ratio of AHC increases, indicating that more oxygen-containing functional groups are generated on the surface of AHC, which is beneficial to improve the surface chemical activity of strong carbon-based materials and provide additional catalytic sites.
[0076] 4 mg of FeNi / AHC-NP catalyst from Example 1 was dispersed in 375 mL of pure water, 125 mL of ethanol solution and 50 mL of Nafion 5% membrane solution, and ultrasonicated for 60 min to obtain a uniformly dispersed suspension. The suspension was drop-coated on the surface of the glassy carbon electrode, with a loading of 453 μg / cm 2 The electrochemical workstation was used to test the -1 The catalyst was tested by cyclic voltammetry in a three-electrode system in a KOH electrolyte solution. The test showed that FeNi / AHC-NP required an overpotential of 290 mV to reach 10 mA cm -2 of current density.
[0077] Application Comparative Example 1
[0078] The difference between the comparative example 1 and the example 1 is that the catalyst used in the comparative example 1 is the FeNi / AHC-N catalyst of the comparative example 1, and the other reaction conditions and test conditions are the same as those of the example 1. It can be seen from the test that FeNi / AHC-N needs an overpotential of 323 mV to reach 10 mA·cm -2 of current density.
[0079] Application Comparative Example 2
[0080] The difference between Application Example 2 and Application Example 1 is that the catalyst used in Application Example 2 is the FeNi / AHC-P catalyst of Application Example 2, and the other reaction conditions and test conditions are the same as those of Application Example 1. It can be seen from the test that FeNi / AHC-P needs an overpotential of 331 mV to reach 10 mA·cm -2 of current density.
[0081] Application Comparative Example 3
[0082] The difference between Application Example 3 and Application Example 1 is that the catalyst used in Application Example 3 is the FeNi / AHC catalyst of Application Example 3, and the other reaction conditions and test conditions are the same as those of Application Example 1. It can be seen from the test that FeNi / AHC needs an overpotential of 549 mV to reach 10 mA·cm -2 of current density.
[0083] Analysis of material catalytic performance
[0084] The catalytic performance of FeNi / AHC-NP catalysts of FeNi / AHC-NP, FeNi / HC-N, FeNi / HC-P and FeNi / HC in Application Example 1 and Comparative Examples 1-3 was analyzed. The analysis results are as follows: Figure 5 shown. Figure 5(a) is the OER-LSV curve, Figure 5 (b) Tafel slope plot. Figure 5 (a) It can be seen that the FeNi / AHC-NP catalyst only needs an overpotential of 290 mV to reach 10 mA cm -2 The current density is better than that of FeNi / AHC-N and FeNi / AHC-P (323 and 331 mV), and much lower than that of FeNi / AHC (549 mV). Figure 5 (b) It can be seen that the Tafel slope corresponding to FeNi / AHC-NP is 66.29 mV·dec -1 , slightly lower than FeNi / AHC-N and FeNi / AHC-P (73.80 and 117.09 mV·dec, respectively). -1 ), but significantly lower than FeNi / AHC (258.11mV·dec -1 ). This indicates that the introduction of nitrogen and phosphorus further improves the OER electrocatalytic activity and reaction kinetics of the FeNi alloy.
[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A nitrogen-phosphorus co-doped iron-nickel based porous biomass carbon catalyst, characterized in that: The biochar is subjected to a hydrothermal reaction to obtain hydrothermal char, which is then subjected to cold alkali activation to obtain cold alkali activated hydrothermal char as a carbon source, on which Fe and Ni are in situ complexed to obtain a precursor, which is then co-doped with N and P, and after high-temperature calcination, a nitrogen-phosphorus co-doped iron-nickel based porous biochar catalyst is obtained.
2. The nitrogen-phosphorus co-doped iron-nickel-based porous biomass carbon catalyst according to claim 1, characterized in that: The nitrogen-phosphorus co-doped iron-nickel-based porous biomass carbon catalyst has a three-dimensional network porous structure and a specific surface area of 160 to 163 m 2 / g, pore volume is 0.15~0.18cm 3 / g, and the average pore size is 5.5~7.4nm.
3. A method for preparing the nitrogen-phosphorus co-doped iron-nickel based porous biomass carbon catalyst as claimed in claim 1 or 2, characterized in that: The following steps are involved: (1) Preparation of hydrothermal charcoal: sugarcane bagasse is added to a hydrochloric acid solution, stirred, and then transferred to a reactor for hydrothermal reaction. After the reaction is completed, the mixture is naturally cooled to room temperature, and the obtained product is washed and dried to obtain hydrothermal charcoal; (2) cold alkali activated hydrothermal carbon: placing the hydrothermal carbon in step (1) in a NaOH solution for cold alkali activation, and after the activation, centrifuging, washing and drying to obtain cold alkali activated hydrothermal carbon; (3) Synthesis of precursor: Fe(NO3)3·9H2O and Ni(CH3COO)2·4H2O are dissolved in water, and after vigorous stirring, the obtained mixed solution is added dropwise to the aqueous solution of cold alkali activated hydrothermal carbon in step (2), and after stirring, the pH of the solution is adjusted to alkaline, and after suction filtration, the obtained product is washed and dried to obtain a precursor; (4) Nitrogen and phosphorus co-doping: The precursor of step (3) is mixed with urea and uniformly ground, and sodium dihydrogen phosphate is added, followed by high-temperature calcination. After the calcination, the mixture is cooled to room temperature to obtain a nitrogen and phosphorus co-doped iron-nickel-based porous biomass carbon catalyst.
4. The method for preparing the nitrogen-phosphorus co-doped iron-nickel based porous biomass carbon catalyst according to claim 3, characterized in that: In step (1), the mass ratio of bagasse to hydrochloric acid solution is 4g:40-45mL, and the concentration of hydrochloric acid solution is 0.1-0.15mol / L.
5. The method for preparing the nitrogen-phosphorus co-doped iron-nickel based porous biomass carbon catalyst according to claim 3, characterized in that: In step (1), the temperature of the hydrothermal reaction is 210-230° C., and the time is 10-12 hours.
6. The method for preparing the nitrogen-phosphorus co-doped iron-nickel based porous biomass carbon catalyst according to claim 3, characterized in that: In step (2), the mass ratio of the hydrothermal charcoal to the NaOH solution is 2.5 g:45-50 mL, the concentration of the NaOH solution is 1.3-1.5 mol / L; and the cold alkali activation time is 1.5-2 h.
7. The method for preparing the nitrogen-phosphorus co-doped iron-nickel based porous biomass carbon catalyst according to claim 3, characterized in that: In step (3), the mass ratio of Fe(NO3)3·9H2O and Ni(CH3COO)2·4H2O is 2.3:1.3-1.6; the mass ratio of cold alkali activated hydrothermal carbon to water in the aqueous solution of cold alkali activated hydrothermal carbon is 1g:100-120mL.
8. The method for preparing the nitrogen and phosphorus co-doped iron-nickel based porous biomass carbon catalyst according to claim 3, characterized in that: In step (4), the mass ratio of the precursor, urea and sodium dihydrogen phosphate is 5:3-4:100-120.
9. The method for preparing the nitrogen-phosphorus co-doped iron-nickel based porous biomass carbon catalyst according to claim 3, characterized in that: In step (4), the high temperature calcination is calcined in a nitrogen atmosphere at 280-300° C. for 1.5-2 hours, and then the temperature is raised to 700-800° C. and maintained for 1.5-2 hours.
10. Use of the nitrogen and phosphorus co-doped iron-nickel based porous biomass carbon catalyst as claimed in claim 1 or 2 in catalytic oxygen evolution reaction.
Citation Information
Patent Citations
FeNi3 composite nitrogen-doped carbon nanotube bifunctional electrocatalyst prepared from biomass
CN114420959A
Method for preparing nitrogen-doped corn straw-based porous carbon material by using two-step activation method
CN116621170A